Boieiras do Ver-o-Peso: tradição, cultura e valores não econômicos da culinária regional na mais importante feira da Amazônia brasileira - Fabrício Khoury Rebello; Paola Corrêa dos Santos; Marcos Antônio Souza dos Santos (Confins)
Inaugurated in 1627, as a goods checkpoint and tax collection in the incipient Amazon economy, the Ver-o-Peso fair was consolidated for contributing to the Pará socioeconomic development from the period of the backcountry drugs, cocoa and rubber cycles to present days. In 1977, the Institute of National Historical and Artistic Heritage (IPHAN) recognized the fair as an architectural and landscape ensemble, being considered the largest free market in Latin America. In this research, it is studied the sector of ready meals sale (Ver-o-Peso boieiras) for the representativeness in the offer of low cost food and of relevant meaning to qualify the food security of its users, as well as for its potential to value aspects of the gastronomy and the tourism of Pará. This provides an opportunity for small entrepreneurs to enter in an important financial market in the contemporary economy. The research was conducted based on a representative sample of the population of Belém, capital of Pará state, in the Brazilian Amazon, with the purpose of analyzing the aspects of consumer perception regarding cultural issues, tourist attractiveness, infrastructure conditions, hygienic-sanitary standards adopted and commercialization of meals offered by the Ver-o-Peso boieiras. The results point out relevant aspects for the increase of human and physical capital (infrastructure and equipment) in the meals sector of Ver-o-Peso fair, in order to meet the standards of enterprise management and food safety required for the activity.